Acoustic Aspects of Sentence Stress in Children with Cochlear Implant - Gouri Shankar Patil; Yamini Sindhura G; R.Madhusudarshan Reddy (Journal of All India Institute of Speech and Hearing, 1970)
The study intended to examine the acoustic features of stress F0, duration, and intensity in children using cochlear implants and compare these features with those in normal hearing children. Seven children with congenital profound hearing impairment fitted with multichannel cochlear implants and equal number of normal hearing children participated in the study. The participants narrated a picture depicting a 'living room' for about 2-3 minutes. The utterances were classified into separate intonation units and primary stressed syllable identified in each intonation unit. The stressed syllables were acoustically analyzed to measure duration, F0, and intensity using Praat software. The statistical analysis was carried out using SPSS version 12.0. The mean duration of primary stressed syllable in children with cochlear implant was 0.32 s (SD = 0.11) and in normal hearing children it was 0.19 s (SD = 0.08). The mean F0 in children with cochlear implant was 339.89 Hz (SD = 56.14) whereas in normal hearing children it was 306.37 Hz (SD = 51.21). The mean intensity was 80.83 dB (SD = 5.49) in children with cochlear implant and 83.51 dB (SD = 5.17) in normal hearing children. The independent samples t- test revealed significant difference between the two groups of participants for all acoustic measures. The results of the current study seem to suggest that children with cochlear implant distinctly produced sentence stress but the acoustic correlates of stress are significantly different from those produced by individuals with normal hearing. Hence, the results emphasize the need to consider inclusion of suprasegmental aspects in the speech-language rehabilitation of children with cochlear implant.